Civil society and democracy in Bangladesh - Khan, Mizanur Rahman; Kabir, Mohammad Humayun. jt. ed. (Dhaka : Academic Press and Publishers in association with Bangladesh Institute of International and Strategic Studies, 2002)
Contributed articles presented at the National Seminar on "Civil Society and Democracy in Bangladesh" held on 28th Sept., 1998, organized by Bangladesh Institute of International and Strategic Studies.
Includes bibliographical references.
Keywords: Bangladesh -- Politics and government